SURVEI TINGKAT KETERAMPILAN SERVIS ATAS PADA SISWI EKSTRAKURIKULER BOLA VOLI SMA SANTO PAULUS SINGKAWANG - sumantri, Edi; ., Imran; Supriatna, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The purpose of research is to obtain information and an overview of: the level of service skills on the volleyball student extracurricular participants at St. Paul High School Singkawang